Role of Calixarene in Chemotherapy Delivery Strategies - Rossella Basilotta; Deborah Mannino; Alessia Filippone; Giovanna Casili; Angela Prestifilippo; Lorenzo Colarossi; Gabriele Raciti; Emanuela Esposito; Michela Campolo (Molecules, 2021)
Since cancer is a multifactorial disease with a high mortality rate, the study of new therapeutic strategies is one of the main objectives in modern research. Numerous chemotherapeutic agents, although widely used, have the disadvantage of being not very soluble in water or selective towards cancerous cells, with consequent side effects. Therefore, in recent years, a greater interest has emerged in innovative drug delivery systems (DDSs) such as calixarene, a third-generation supramolecular compound. Calixarene and its water-soluble derivatives show good biocompatibility and have low cytotoxicity. Thanks to their chemical–physical characteristics, calixarenes can be easily functionalized, and by itself can encapsulate host molecules forming nanostructures capable of releasing drugs in a controlled way. The encapsulation of anticancer drugs in a calixarene derivate improves their bioavailability and efficacy. Thus, the use of calixarenes as carriers of anticancer drugs could reduce their side effects and increase their affinity towards the target. This review summarizes the numerous research advances regarding the development of calixarene nanoparticles capable of encapsulating various anticancer drugs.